Polityczne public relations w podczas kampanii wyborczych w III RP - Kardaś, Jarosław (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Creating the image of politicians is always a deliberate act. PR should be a reliable source of information about politicians or party. Very often the image of a political party or a politician is being built exclusively on the basis of media coverage. It seems that success in politics inevitably connects with a good presentation in the media. The experience of Polish political PR is only 25 years old. This can not be compared with the experiences of western countries, especially the United States. However, even in this period, we have seen a very well-run election campaigns, but also those which were conducted incompetently.